A SPEECH ACT ANALYSIS OF TEACHER TALK IN AN EFL CLASSROOM - Basra, Sri Meiweni; Thoyyibah, Luthfiyatun (International Journal of Education, 2017)
The inappropriate use of speech act in EFL classroom may lead to misunderstanding due to the distinct cultures between the origin of language and the users. The purposes of the research are to find out speech act classification mostly used by an EFL teacher while teaching, the reason of why certain classification was preferred and the implication of the selected speech act classification toward the teaching and learning process. This research is a case study research involving an English teacher teaching an EFL class. The study uses Searle’s taxonomy of speech act classification as the instrument. The findings of the research show the frequency of each classification found as the following: 70% for directives, 21% for representative, 6% for expressive and 3% for commissive. Directive speech acts are used mostly by the teacher because the teacher adopts the principle of Communicative Language Teaching. The use of directive speech act apparently make implication towards the improvement of the students’ productive skills. The study concludes that the choice of speech acts classification determine the teaching approach and vice versa. It is recommended for English teachers wishing to help students to achieve communicative competence to use more directive speech acts.